Response of surface ozone over the continental United States to UV radiation declines from the expected recovery of stratospheric ozone. Issue 1 (December 2018) - Hodzic, A.; Madronich, S.
Abstract The response of surface ozone concentrations to decreases in ultraviolet (UV) radiation that are expected from the recovery of stratospheric ozone by the end of the twenty-first century is examined with the regional WRF–Chem model. The study is performed over the continental United States for the summer of 2010 at 12 km horizontal resolution which, compared to previous studies, allows a better separation of chemical regimes that exhibit opposite responses to UV radiation changes. Our results show that on the regional scale, surface ozone is expected to increase by 0.5 to 1 ppb due to its slower destruction, while the opposite can be seen in the vicinity of some urban centers where ozone concentrations could decrease by up to 1 ppb due to its slower photochemical production. Geographic overlay with population shows however a relatively small net increase in exposure of 0.4 ppb, with an asymmetric distribution characterized by some disbenefit to the majority of the US population and a benefit to a relatively small fraction ( 4%) of population. ATMOSPHERIC SCIENCE: Surface ozone exposure The future population of the United States may see increasing exposure to poor air quality. Surface ozone — produced by the photolysis of nitrogen oxides and volatile organic compounds — forms a significant atmospheric pollutant with widely recognized detrimental health impacts. Alma Hodzic and Sasha Madronich from the National Center for Atmospheric Research, USA, use a high resolution regional climate model (WRF-Chem) to investigate how future changes in UV radiation impact surface ozone production — and thus air quality — over the continental United States. While urban centres experience reductions in surface ozone by up to 1 ppb by the end of the 21st century, increases of the same magnitude are expected in other locations, on balance increasing population exposure to surface ozone. Enhanced mitigation action is therefore required to improve future air quality and limit health impacts.